Numerical and Experimental Study on the Multiobjective Optimization of a Two-Disk Flexible Rotor System - Zheng Longxi; Jia Shengxi; Huang Jingjing (International Journal of Rotating Machinery)
With the ever-increasing requirement for the thrust to weight ratio, the rotational speed of modern aeroengine is increasingly improved; thus most of the aeroengine rotor is flexible. Some dynamic problems, such as excessive vibration, appear due to the increase of the rotation speed of the aeroengine. The aim of this study is to reduce the vibration level of the flexible rotor system through optimum design. A laboratory scale two-disk flexible rotor system representing a typical aeroengine rotor system is designed. A combinational optimization strategy coupling the rotordynamics calculation software ANSYS and the multidisciplinary optimization software ISIGHT is proposed to optimize the rotor system. The positions of the disks are selected as the design variables. Constraints are imposed on critical speeds. The disks’ amplitudes and bearings’ transmitted forces are chosen as the optimization objectives. Using this strategy, the optimal positions of the two disks are obtained. The numerical optimization results are verified by the experiments based on the test rig. The results show a significant vibration level reduction after optimization.